Generative spaces of gender and feminist geography in Singapore: entanglements of the personal and political. Issue 7 (2nd September 2019) - Huang, Shirlena; Ramdas, Kamalini
Abstract: While geographers' work in Southeast Asia has yet to engage substantively with theoretical developments in gender/feminist studies generated by Anglo-American academic centers, we argue that Singapore has proven to be somewhat of an exception. Focusing on the National University of Singapore, this article discusses how the development of gender and feminist geography in Singapore has benefitted from being able to engage with international debates in feminism through the country's and NUS' internationalization efforts, and working in the English language. Using the notion of generative spaces, we highlight first, the importance of using our teaching to engage in feminist activism to encourage feminist change in the classroom, as well as within our immediate communities and further afield; and second, the nascent yet significant contributions of feminist geographers based in Singapore to feminist theorization from and about the Global South.